Phase change energy storage type cement-based composite material PCM-UHPC and preparation method thereof

By introducing phase change materials of microcapsule encapsulated in UHPC, the problem of traditional UHPC lacking temperature control and insulation performance is solved, and the combination of efficient energy storage temperature regulation and mechanical properties is achieved, which is suitable for building energy-saving and temperature control projects.

CN119528518APending Publication Date: 2025-02-28THE FOURTH OF CHINA EIGHTH ENG BUREAU
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411780636.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional UHPC lacks temperature control and insulation properties, and the fluidity and leakage of PCM make it difficult to directly apply to cement-based materials.

Method used

Using microcapsule packaging technology, phase change material is encapsulated in microcapsules that are composited with polymer and nano-inorganic materials, and introduced into ultra-high performance cement-based materials to form phase change energy storage cement-based composite PCM-UHPC.

Benefits of technology

It improves the energy storage and temperature regulation performance of the material, maintains high strength and high durability, has significant energy-saving effects, high thermal stability, and excellent anti-leakage and anti-aging properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to a phase change energy storage type cement-based composite material PCM-UHPC, which comprises an ultra-high performance cement-based material (UHPC) matrix and a microencapsulated phase change energy storage material (PCM microcapsule), a microcapsule wall material of the microencapsulated phase change energy storage material (PCM microcapsule) is compounded by a polymer and a nano inorganic material, and the polymer and the nano inorganic material are compounded to form the phase change energy storage type cement-based composite material PCM-UHPC. Wherein the ultra-high performance cement-based material (UHPC) matrix is composed of Portland cement, silica fume, fly ash, quartz powder, quartz sand and a water reducing agent. The material has the energy storage and heat preservation performance and the ultrahigh mechanical property, temperature regulation and energy balance can be achieved in the environment with large temperature difference changes, heating and refrigerating energy consumption of buildings is reduced, and the material has high thermal stability and long service life and is suitable for engineering structures such as building energy saving and temperature control bridges and tunnels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a phase-change energy storage cement-based composite material PCM-UHPC and a preparation method thereof. Background Art

[0002] With the increasing demand for energy conservation and green buildings, building materials are developing towards multifunctionality and intelligence. Ultra-high performance cement-based material UHPC, as a cement-based composite material with high strength, low porosity and high durability, is widely used in construction and infrastructure. However, traditional UHPC mainly focuses on mechanical properties and durability, and lacks temperature control and thermal insulation properties. Phase change material PCM, as a high-efficiency energy storage material, can regulate temperature fluctuations through the phase change process and is suitable for application in the field of building energy conservation.

[0003] Introducing PCM into UHPC to prepare PCM-UHPC composite materials with thermal insulation and energy storage functions can achieve a combination of mechanical properties and temperature regulation properties. It is a key material for future green buildings and infrastructure construction. However, due to the fluidity and permeability of PCM, its direct application in cement-based materials has certain difficulties. By adopting microcapsule encapsulation technology and combining polymer and inorganic nanomaterial composite wall materials, the leakage and chemical aging problems of PCM can be effectively solved, and the thermal cycle stability and interface bonding strength of PCM can be improved. Summary of the invention

[0004] The purpose of the present invention is to solve the following shortcomings in the prior art: traditional UHPC mainly focuses on mechanical properties and durability, lacks temperature control and thermal insulation performance, and has certain difficulties in its direct application in cement-based materials due to the fluidity and permeability of PCM. The phase change energy storage cement-based composite material PCM-UHPC and its preparation method are proposed.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The phase change energy storage cement-based composite material PCM-UHPC comprises an ultra-high performance cement-based material (UHPC) matrix and a microencapsulated phase change energy storage material (PCM microcapsule), wherein the microcapsule wall material of the microencapsulated phase change energy storage material (PCM microcapsule) is a composite of a polymer and a nano-inorganic material.

[0006] Preferably, the ultra-high performance cement-based material (UHPC) matrix is ​​composed of silicate cement, silica fume, fly ash, quartz powder, quartz sand and water reducer, and the ultra-high performance cement-based material (UHPC) matrix is ​​composed of the following components in mass percentage: 35-40% silicate cement, 5-10% silica fume, 10-15% fly ash, 20-30% quartz powder, 10-20% quartz sand, and 1-2% water reducer.

[0007] Preferably, the microencapsulated phase change energy storage material (PCM microcapsule) material is configured as microencapsulated paraffin or hydrated salt phase change material.

[0008] Preferably, the microcapsule wall material of the microencapsulated phase change energy storage material (PCM microcapsule) is composed of polyurethane (PU) and nano silicon dioxide (SiO ) composite composition.

[0009] A method for preparing a phase change energy storage cement-based composite material PCM-UHPC includes the preparation of the microencapsulated phase change energy storage material (PCM microcapsule) and the preparation of the phase change energy storage cement-based composite material PCM-UHPC. The preparation of the microencapsulated phase change energy storage material (PCM microcapsule) includes the following steps: S1: Pretreatment of phase change material: heating the selected phase change material (such as paraffin) to 35-60°C until it is completely liquefied and set aside; S2: Nano-silica dispersion: 0.5-2 wt% nano-silica was added to 5-10 wt% polyurethane solution and ultrasonic dispersion was performed for 15-30 minutes (100-300 W power) until a uniformly dispersed polyurethane / SiO2 solution was formed. Composite solution; S3: Emulsification process: gradually add the liquid phase change material into the polyurethane solution, control the stirring speed at 500-1500rpm, and continue for 10-20 minutes to form a stable emulsion. Control the stirring speed and adjust it between 500-1500rpm according to the microcapsule particle size requirements; S4: Cross-linking polymerization reaction: add 0.1-0.5 wt% of a cross-linking agent (such as calcium chloride) to the emulsion, control the temperature at 40-60°C, and continue stirring for 30-60 minutes to ensure that the cross-linking reaction is complete. Monitor the viscosity and temperature of the system during the polymerization reaction to ensure that the polyurethane can be completely cross-linked; S5: washing and drying: after centrifuging the prepared microcapsules, wash them with pure water or ethanol for 3-5 times to remove the residual unreacted substances, and dry the washed microcapsules at 50-80°C for 4-8 hours to ensure the evaporation of water and the stability of the microcapsule structure.

[0010] Preferably, the preparation of the phase change energy storage cement-based composite material PCM-UHPC comprises the following steps: S1: Premixing of cement-based materials: Weigh silicate cement, silica fume, fly ash, quartz powder, quartz sand and water reducing agent, premix all dry materials for 3-5 minutes to ensure uniform distribution, and form cement-based material powder; S2: Addition of microencapsulated phase change energy storage material (PCM microcapsule): Add microencapsulated phase change energy storage material (PCM microcapsule) into the mixed cement-based material powder at a ratio of 3-5 wt% (based on the total weight of cement-based material). Too high an amount may affect the mechanical properties, while too low an amount may result in insufficient energy storage effect. Therefore, 3-5% is selected as the optimal balance point. Mixing is performed at a low speed (150-180 rpm) for 5-10 minutes to avoid damage to the microcapsules and ensure uniform distribution of PCM in the matrix. S3: Preparation of cement paste: Add 18-2wt% of mixing water to UHPC cementitious material, and add 1-2 wt% of water reducer to improve the fluidity of the material, stir efficiently for 5-10 minutes until the paste is uniform, and control the stirring speed at 300-360rpm to avoid the microcapsules from breaking during strong stirring; S4: Molding and curing: Pour the prepared slurry into the mold and vibrate it gently to expel bubbles. Cure it in a humid environment for 24 hours to prevent the material from losing water at an early stage. After demolding, cure the specimen under standard conditions of 20°C and 95% humidity for 28 days to ensure complete hydration of the cement-based material and achieve the expected mechanical properties.

[0011] Among the cement-based materials, silicate cement accounts for 35-40 wt%, serving as the main cementitious material to provide matrix strength; Silica fume: accounts for 5-10 wt%, which plays a role in enhancing the density of the material, filling the pores of the cement matrix, and improving impermeability and durability; Fly ash: 10-15 wt%, improves workability and reduces shrinkage, increasing the durability of the cement matrix; Quartz powder: accounts for 20-30 wt%, enhances the filling density of the material and improves the compressive strength; Quartz sand: 10-20 wt%, used as aggregate to provide support and strength; Water reducing agent: accounts for 1-2 wt%, used to enhance the fluidity of the material, ensure the uniformity of the slurry and facilitate molding.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The phase change energy storage thermal insulation ultra-high performance cement-based composite material PCM-UHPC provided by the present invention improves the energy storage and temperature regulation performance of the material by introducing microcapsule phase change materials into UHPC, while maintaining high strength and high durability. The material of the present invention has the characteristics of significant energy-saving effect, high thermal stability, excellent anti-leakage and anti-aging properties, etc., and is suitable for the fields of building energy conservation, temperature-controlled bridges and tunnel engineering, and has broad application prospects. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0014] The phase change energy storage cement-based composite material PCM-UHPC includes an ultra-high performance cement-based material (UHPC) matrix and a microencapsulated phase change energy storage material (PCM microcapsule), wherein the microcapsule wall material of the microencapsulated phase change energy storage material (PCM microcapsule) is a composite of polymer and nano-inorganic material.

[0015] The ultra-high performance cement-based material (UHPC) matrix is ​​composed of silicate cement, silica fume, fly ash, quartz powder, quartz sand and water reducer. The ultra-high performance cement-based material (UHPC) matrix is ​​composed of the following components in mass percentage: 35-40% silica fume, 5-10% silica fume, 10-15% fly ash, 20-30% quartz powder, 10-20% quartz sand and 1-2% water reducer.

[0016] The PCM microcapsule is a microcapsule-encapsulated paraffin or hydrated salt phase change material. The microcapsule wall material of the PCM microcapsule is composed of polyurethane (PU) and nano-silicon dioxide (SiO ) composite composition.

[0017] A method for preparing a phase change energy storage cement-based composite material PCM-UHPC includes preparing a microencapsulated phase change energy storage material (PCM microcapsule) and preparing a phase change energy storage cement-based composite material PCM-UHPC. The preparation of the microencapsulated phase change energy storage material (PCM microcapsule) includes the following steps: S1: Pretreatment of phase change material: heating the selected phase change material (such as paraffin) to 35-60°C until it is completely liquefied and set aside; S2: Nano-silica dispersion: 0.5-2 wt% nano-silica was added to 5-10 wt% polyurethane solution and ultrasonic dispersion was performed for 15-30 minutes (100-300 W power) until a uniformly dispersed polyurethane / SiO2 composite solution was formed; S3: Emulsification process: gradually add the liquid phase change material into the polyurethane solution, control the stirring speed at 500-1500rpm, and continue for 10-20 minutes to form a stable emulsion. Control the stirring speed and adjust it between 500-1500rpm according to the microcapsule particle size requirements; S4: Cross-linking polymerization reaction: add 0.1-0.5 wt% of a cross-linking agent (such as calcium chloride) to the emulsion, control the temperature at 40-60°C, and continue stirring for 30-60 minutes to ensure that the cross-linking reaction is complete. Monitor the viscosity and temperature of the system during the polymerization reaction to ensure that the polyurethane can be completely cross-linked; S5: washing and drying: after centrifuging the prepared microcapsules, wash them with pure water or ethanol for 3-5 times to remove the residual unreacted substances, and dry the washed microcapsules at 50-80°C for 4-8 hours to ensure the evaporation of water and the stability of the microcapsule structure.

[0018] The preparation of phase change energy storage cement-based composite material PCM-UHPC includes the following steps: S1: Premixing of cement-based materials: Weigh silicate cement, silica fume, fly ash, quartz powder, quartz sand and water reducing agent, premix all dry materials for 3-5 minutes to ensure uniform distribution, and form cement-based material powder; S2: Addition of microencapsulated phase change energy storage material (PCM microcapsule): Add microencapsulated phase change energy storage material (PCM microcapsule) into the mixed cement-based material powder at a ratio of 3-5 wt% (based on the total weight of cement-based material). Too high an amount may affect the mechanical properties, while too low an amount may result in insufficient energy storage effect. Therefore, 3-5% is selected as the optimal balance point. Mixing is performed at a low speed (150-180 rpm) for 5-10 minutes to avoid damage to the microcapsules and ensure uniform distribution of PCM in the matrix. S3: Preparation of cement paste: Add 18-2wt% of mixing water to UHPC cementitious material, and add 1-2 wt% of water reducer to improve the fluidity of the material, stir efficiently for 5-10 minutes until the paste is uniform, and control the stirring speed at 300-360rpm to avoid the microcapsules from breaking during strong stirring; S4: Molding and curing: Pour the prepared slurry into the mold and vibrate it gently to expel bubbles. Cure it in a humid environment for 24 hours to prevent the material from losing water at an early stage. After demolding, cure the specimen under standard conditions of 20°C and 95% humidity for 28 days to ensure complete hydration of the cement-based material and achieve the expected mechanical properties.

[0019] Among cement-based materials, Portland cement accounts for 35-40 wt%, serving as the main cementitious material and providing matrix strength; Silica fume: accounts for 5-10 wt%, which plays a role in enhancing the density of the material, filling the pores of the cement matrix, and improving impermeability and durability; Fly ash: 10-15 wt%, improves workability and reduces shrinkage, increasing the durability of the cement matrix; Quartz powder: accounts for 20-30 wt%, enhances the filling density of the material and improves the compressive strength; Quartz sand: 10-20 wt%, used as aggregate to provide support and strength; Water reducing agent: accounts for 1-2 wt%, used to enhance the fluidity of the material, ensure the uniformity of the slurry and facilitate molding. Example 1

[0020] Preparation of microencapsulated phase change energy storage materials (PCM microcapsules): Raw materials: paraffin (melting point 28 ° C, latent heat 180 J / g), polyurethane (PU), nano silicon dioxide (SiO ).

[0021] Preparation method: S1: Heat the paraffin to 35 degrees Celsius and keep it in liquid state for later use; S2: 0.5% nano-silica was added to the polyurethane solution and ultrasonically dispersed for 15 minutes to form a uniform solution; S3: adding liquid paraffin into the wall material solution by emulsification method, and stirring at high speed to form an emulsion; S4: Add 0.2% of the cross-linking agent and keep stirring for 60 minutes to form microencapsulated PCM, and obtain the finished product after centrifugation, washing and drying.

[0022] Preparation of PCM-UHPC composite materials: Raw materials: microencapsulated paraffin, silicate cement, silica fume, fly ash, quartz powder, quartz sand, water reducing agent.

[0023] Preparation method: S1: microencapsulated paraffin prepared according to Example 1, with an admixture amount of 4% of the total weight of the cement-based material; S2: Proportion: Portland cement 35%, silica fume 8%, fly ash 12%, quartz powder 25%, quartz sand 17%, water reducer 1%, microencapsulated PCM 4%; S3: Add microencapsulated phase change energy storage material (PCM microcapsule) to the powder and mix evenly, add water to stir into slurry, pour into the mold and cure for 28 days.

[0024] Test Results Mechanical properties: The compressive strength is about 130 MPa, and the flexural strength is about 15 MPa. Compared with traditional UHPC, the mechanical properties are slightly lower, but meet the engineering requirements.

[0025] Energy storage performance: At a temperature difference of 20-35°C, energy storage performance is improved by 30% and temperature fluctuation is reduced by 2-3°C.

[0026] Thermal cycle stability: After 100 thermal cycles, there is no leakage of PCM and no obvious attenuation of latent heat of phase change.

[0027] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Phase change energy storage cement-based composite material PCM-UHPC, characterized in that: It includes an ultra-high performance cement-based material (UHPC) matrix and a microencapsulated phase change energy storage material (PCM microcapsule), wherein the microcapsule wall material of the microencapsulated phase change energy storage material (PCM microcapsule) is a composite of polymer and nano inorganic material.

2. The phase change energy storage cement-based composite material PCM-UHPC according to claim 1, characterized in that: The ultra-high performance cement-based material (UHPC) matrix is ​​composed of silicate cement, silica fume, fly ash, quartz powder, quartz sand and water reducing agent. The ultra-high performance cement-based material (UHPC) matrix is ​​composed of the following components in mass percentage: 35-40% silicate cement, 5-10% silica fume, 10-15% fly ash, 20-30% quartz powder, 10-20% quartz sand and 1-2% water reducing agent.

3. The phase change energy storage cement-based composite material PCM-UHPC according to claim 1, characterized in that: The microencapsulated phase change energy storage material (PCM microcapsule) is configured as a microencapsulated paraffin or hydrated salt phase change material.

4. The phase change energy storage cement-based composite material PCM-UHPC according to claim 1, characterized in that: The microcapsule wall material of the microencapsulated phase change energy storage material (PCM microcapsule) is composed of polyurethane (PU) and nano silicon dioxide (SiO ) composite composition.

5. A method for preparing the phase change energy storage cement-based composite material PCM-UHPC according to any one of claims 1 to 4, characterized in that: The method includes the preparation of the microencapsulated phase change energy storage material (PCM microcapsule) and the preparation of the phase change energy storage cement-based composite material PCM-UHPC. The preparation of the microencapsulated phase change energy storage material (PCM microcapsule) includes the following steps: S1: Pretreatment of phase change material: heating the selected phase change material (such as paraffin) to 35-60°C until it is completely liquefied and set aside; S2: Nano-silica dispersion: 0.5-2 wt% nano-silica was added to 5-10 wt% polyurethane solution and ultrasonic dispersion was performed for 15-30 minutes (100-300 W power) until a uniformly dispersed polyurethane / SiO2 composite solution was formed; S3: Emulsification process: gradually add the liquid phase change material into the polyurethane solution, control the stirring speed at 500-1500rpm, and continue for 10-20 minutes to form a stable emulsion. Control the stirring speed and adjust it between 500-1500rpm according to the microcapsule particle size requirements; S4: Cross-linking polymerization reaction: add 0.1-0.5 wt% of a cross-linking agent (such as calcium chloride) to the emulsion, control the temperature at 40-60°C, and continue stirring for 30-60 minutes to ensure that the cross-linking reaction is complete. Monitor the viscosity and temperature of the system during the polymerization reaction to ensure that the polyurethane can be completely cross-linked; S5: washing and drying: after centrifuging the prepared microcapsules, wash them with pure water or ethanol for 3-5 times to remove the residual unreacted substances, and dry the washed microcapsules at 50-80°C for 4-8 hours to ensure the evaporation of water and the stability of the microcapsule structure.

6. The method for preparing the phase change energy storage cement-based composite material PCM-UHPC according to claim 5, characterized in that: The preparation of the phase change energy storage cement-based composite material PCM-UHPC comprises the following steps: S1: Premixing of cement-based materials: Weigh silicate cement, silica fume, fly ash, quartz powder, quartz sand and water reducing agent, premix all dry materials for 3-5 minutes to ensure uniform distribution, and form cement-based material powder; S2: Addition of microencapsulated phase change energy storage material (PCM microcapsule): Add microencapsulated phase change energy storage material (PCM microcapsule) into the mixed cement-based material powder at a ratio of 3-5 wt% (based on the total weight of cement-based material). Too high an amount may affect the mechanical properties, while too low an amount may result in insufficient energy storage effect. Therefore, 3-5% is selected as the optimal balance point. Mixing is performed at a low speed (150-180 rpm) for 5-10 minutes to avoid damage to the microcapsules and ensure uniform distribution of PCM in the matrix. S3: Preparation of cement paste: Add 18-2wt% of mixing water to UHPC cementitious material, and add 1-2 wt% of water reducer to improve the fluidity of the material, stir efficiently for 5-10 minutes until the paste is uniform, and control the stirring speed at 300-360rpm to avoid the microcapsules from breaking during strong stirring; S4: Molding and curing: Pour the prepared slurry into the mold and vibrate it gently to expel bubbles. Cure it in a humid environment for 24 hours to prevent the material from losing water at an early stage. After demolding, cure the specimen under standard conditions of 20°C and 95% humidity for 28 days to ensure complete hydration of the cement-based material and achieve the expected mechanical properties.

7. The method for preparing the phase change energy storage cement-based composite material PCM-UHPC according to claim 6, characterized in that: Among the cement-based materials, silicate cement accounts for 35-40 wt%, serving as the main cementitious material to provide matrix strength; Silica fume: accounts for 5-10 wt%, which plays a role in enhancing the density of the material, filling the pores of the cement matrix, and improving impermeability and durability; Fly ash: 10-15 wt%, improves workability and reduces shrinkage, increasing the durability of the cement matrix; Quartz powder: accounts for 20-30 wt%, enhances the filling density of the material and improves the compressive strength; Quartz sand: 10-20 wt%, used as aggregate to provide support and strength; Water reducing agent: accounts for 1-2 wt%, used to enhance the fluidity of the material, ensure the uniformity of the slurry and facilitate molding.

Citation Information

Cited By

  • PCM-based energy storage building material and preparation method thereof

    CN119954479A

  • A PCM-based energy storage building material and its preparation method

    CN119954479B